Utilization Community-Based Rehabilitation Methods to Improve Independence and Quality of Life for Patients with Disabilities in Nara Phirom Health Promoting Hospital, Thailand - Dwi Rosella Komalasari; Umi Budi Rahayu; Suryo Saputra Perdana; Pakaratee Chaiyawat; Nikmatur Rosidah (Universitas Muhammadiyah Surakarta, 2024)
The disability community activity, Nara Phirom Health Promoting Hospital in Banglen District, Nakhon Pathom, Thailand, collaborated with the Faculty of Physiotherapy, Mahidol University to support the disability community. Using the Community-based rehabilitation (CBR) method, the aim to enhance independence and quality of life. Evaluation includes IADL for independence and WHOQoL Bref-100 for quality of life. Education on health, immobilization, and exercise was provided to patients, families, and caregivers. Therapists teached physical exercises, to be repeated 2-3 times daily by caregivers and family. The 1-month program, supervised by therapists, includes standing and walking for patients with lower extremity strength of 3/5 (measured by manual muscle testing). Rehabilitation involves crafting items like wallets and bags, stamps, and flowers from bottles. Results, patients with low function status (very dependent on other people) decreased by 64.3%, moderate function increased by 116.7% and independence increased by 111.1%. There was a significant improvement in quality of life (WHOQoL) and all domains after CBR program.